Freezing/thawing effects on the exfoliation of montmorillonite in gelatin‐based bionanocomposite. Issue 5 (17th September 2012) - Mu, Changdao; Li, Xinying; Zhao, Yige; Zhang, Hanguang; Wang, Liangjie; Li, Defu
Abstract Freezing/thawing is used as a new method to elaborate exfoliated gelatin‐Montmorillonite (MMT) bionanocomposites. The data of X‐ray diffraction and transmission electron microscopy indicate that freezing/thawing is an effective approach to exfoliate the clay for concentrations higher than 5 mass% in gelatin matrix. In addition, after freezing/thawing process to introduce, the crystallinity (triple‐helix content) of gelatin‐MMT bionanocomposites is improved, revealing that freezing/thawing method has the advantages for gelatin molecules to renature into triple‐helix. Specially, the data of Fourier transform infrared indicate that freezing/thawing may be induce more hydrogen bond interactions in gelatin‐MMT bionanocomposites due to the better dispersion of MMT. The mechanical measurements and thermogravimetric analysis show that gelatin‐MMT bionanocomposites prepared by freezing/thawing display enhanced mechanical properties and thermal stability in comparison with the ones prepared by conventional blending at the same clay content. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013